Coup de dés (collection) books and ideas after Mallarmé - Pichler, Michalis 1980-; Gilbert, Annette 1975-; Dworkin, Craig 1969-; Boltanski, Luc 1940-; Esquerre, Arnaud 1975-; Sekiguchi, Ryōko 1970- (Spector Books, 2024)
Coup de dés (Collection): Books and Ideas after Mallarmé brings together a vast number of editions of Mallarmé’s chef d’uvre as well as many of its historical and contemporary editions and appropriations by other authors. Mallarmé’s arrangement of the poem on opposite pages turned each side into a compositional entity. Constellations of words on a spread and the interplay between the text fragments and the surrounding white—similar to the way a constellation of stars interacts with the sky—was a metaphor explicitly used and introduced into literature by Mallarmé. His notion of "constellation", for example, is connected to Ulises Carrión’s vision of a "new" book. "In the old art, to read the last page takes as much time as to read the first one./In the new art the reading rhythm changes, quickens, speeds up," as he wrote in 1975. The richly illustrated book contextualizes the perception and appropriations of Mallarmé’s masterpiece through critical essays written by the editor and leading scholars such as Annette Gilbert, Craig Dworkin, Luc Boltanski/Arnaud Esquerre, and Ryoko Sekiguchi
Impring: Published on the occasion of the exhibition "Exposition littéraire autour de Mallarmé" at Center for Book Arts, January 18 - May 1, 2024
Keywords: Mallarmé, Stéphane -- 1842-1898 -- Un coup de dés jamais n'abolira le hasard; Geschichte; Rezeption; Dichtung -- Begriff; Typografie; Edition; Mallarmé; Textkunst; Lyrik; Ausstellungskatalog -- Center for Book Arts -- 18.01.2024-01.05.2024 -- New York, NY